Editorial Special Issue on Corporate Governance - Greg Jones; Claire Beattie; Afzalur Rashid (Australasian Accounting, Business and Finance Journal, 2017)
Editorial March 2017
Keywords: Editorial; 2017; Special issue; corporate governance